CPET : Gambaran Umum dan Penggunaan pada Pasien Gagal Jantung - Suprapta, Aloysius; Listyoko, Aditya; Djajalaksana, Susanthy (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Cardiopulmonary exercise test (CPET) is a non-invasive modality used to assess a person's exercise capacity. An assessment of the gas exchange mechanism that occurs in the breath-to-breath stage of respiration will describe gas exchange at the cellular level. Monitoring of gas exchange is a parameter in assessing abnormalities that cause disruption of aerobic metabolic processes in the body. These parameters in CPET assist clinicians in sorting and assessing the factors that cause dyspnea or fatigue during activity, whether disorders on the respiratory system, cardiovascular system, or muskuloskeletal side. In addition, CPET is also a modality in determining the prognosis and feasibility of heart transplantation in clients with heart failure. Peak VO2 assessment 14 mL/kg/min gave a better picture of cumulative survival in heart failure patients, and O2 pulse 10 mL/beat showed better event-free survival.